Estado trófico y monitoreo de variables limnológicas en un lago artificial (Lago del Fuerte, Tandil, prov. de Buenos Aires) - Albornoz, H. (2009)
“Del Fuerte” Lake (about 20 acres). It is used for recreation and tourism. During the researches which have been made since1995 to 2005, it was determined that the lake is eutrophicated. The aim of this study is to update the levels of trophic state of the lake and explore the relationship between chlorophyll-a concentration and secchi disk depth. The method of Trophic State Index of Carlson and the OCDE index was applied, and the data was collected in two sampling zones every 15 days. The result of this study was the collection of 22 samples from October 2007 until today. Comparing the sampling zones, they proved not significant differences of (p>0.05). With respect to larger chlorophyll values (13 μg/l), the secchi disk depth changes temporarily, with very small effect on secchi disk depth (0.08 m); showing nonchlorophyll light absorption. Comparing summer and winter, they proved not significant differences of (p>0.05), except temperature (p<0.05). The condition of the lake is confirmed as Eutrophic, according to the TSI index, (TSI=78 of secchi disk depth and TSI=74 of chlorophyll-a); and Hipereutrophic according to OCDE (secchi disk depth=0.56m; chlorophyll-a=66 (μg/l).